2014
DOI: 10.2174/1871526514666140827101231
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Response of Osteoblasts to Doxycycline in an Inflammatory Model Induced by C-reactive Protein and Interleukin-6

Abstract: Objectives: Investigation of osteoblastic responses to oxidative stress, induced by C-reactive protein (CRP) and IL-6 and ameliorating effects of doxycycline (Dox); using assays for 5-alpha dihydrotestosterone (DHT) as an antioxidant marker of healing. IL-6 and CRP are risk markers of periodontitis and prevalent comorbidities in periodontitis subjects. Methods: Confluent monolayer cultures of osteoblasts were incubated with radiolabelled testosterone (14C-T) as substrate, in the presence or absence (Control) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…In biochemical studies, DCNP opt was significant to diminish the level of TNF-a and lipid peroxidation, while increased GSH level as compared to pure doxycycline hydrochloride and ketamine resulting in improved anti-inflammatory and antioxidant effects; thus, better pharmacodynamic effects due to improved bioavailability in brain. Moreover, available literature on anti-inflammatory (Tilakaratne & Soory, 2014;Omolu et al, 2017) and antioxidant (Antonio et al, 2014) effects of doxycycline hydrochloride supports our study. These observations collectively suggest the protective effect of DNCP opt against depressive symptoms of psychosis at lower dose.…”
Section: Discussionsupporting
confidence: 85%
“…In biochemical studies, DCNP opt was significant to diminish the level of TNF-a and lipid peroxidation, while increased GSH level as compared to pure doxycycline hydrochloride and ketamine resulting in improved anti-inflammatory and antioxidant effects; thus, better pharmacodynamic effects due to improved bioavailability in brain. Moreover, available literature on anti-inflammatory (Tilakaratne & Soory, 2014;Omolu et al, 2017) and antioxidant (Antonio et al, 2014) effects of doxycycline hydrochloride supports our study. These observations collectively suggest the protective effect of DNCP opt against depressive symptoms of psychosis at lower dose.…”
Section: Discussionsupporting
confidence: 85%
“…It has been reported that doxycycline prevents periodontal tissue breakdown by inhibiting local and systemic oxidative stress 35) , which in turn helps promote bone regeneration by activating osteoblastogenesis 36) .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, IL6 signaling in osteoblasts inhibits the formation of 5-alpha dihydrotestosterone (DHT), which is an anabolic hormone important for the formation of new bone tissue. Of note, the inhibition of bone formation by IL6 was reverted by doxycycline [ 105 ]. The importance of targeting IL6 levels and/or its signaling as a therapeutic approach gains further importance when considering the evidence that this cytokine induces the osteoblast transition of vascular smooth muscle cells with the calcification of vessels and increased cardiovascular and renal risk [ 106 ].…”
Section: Indirect Effects Of Infection On Bone Metabolismmentioning
confidence: 99%